Nuorten ateriarytmi kouluviikon aikana ja siihen yhteydessä olevat tekijät. - TASKINEN, KIRSI; RANTANEN, ANJA; JORONEN, KATJA (Hoitotiede, 2022)
The purpose of this nationally representative cross-sectional study was to describe how regularly adolescents eat during a school week, how sociodemographic and family factors are associated with adolescents' meal frequency, and the relationship between energy drink consumption and adolescents' meal frequency. The target group was 8th and 9th graders of the comprehensive school and the School Health Promotion study from 2017 was used as data (n=73,680). The data was analysed using statistical methods, such as chi square test and multinomial logistic regression analysis. Of the adolescents, 64% had a regular meal frequency, 4% had irregular meal frequency and 32% had neither regular nor irregular meal frequency. 7% of boys and 3% of girls consumed energy drinks on 6-7 days of a week. According to the adjusted multinomial logistic regression, among both boys and girls, single parent families, joint custody families, low educational status of mothers, foreign background, little time spent together with the family, lower interaction with parents, and daily consumption of energy drinks were associated with irregular meal frequency. In conclusion, those working with adolescents should raise discussion, for instance in the comprehensive health examinations, the meal frequency, the use of energy drinks, and the essential role of the supportive parent-adolescent interaction when the young person is making health choices.